2008
DOI: 10.1080/00036840600892886
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and economic growth nexus: a time-series evidence from India

Abstract: This study examines the relationship between financial development and economic growth in India for the period 1951-52 to 1995-96. The long-run equilibrium and short-run dynamic models are estimated using financial interrelations ratio and new issue ratio as the measures of financial development, a la Goldsmith (1969). The Johansen (1991) estimator rejects the null of zero cointegrating vector and shows the presence of long-run equilibrium relationship between financial development and economic growth. The err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 41 publications
(60 reference statements)
4
31
1
4
Order By: Relevance
“…This result implies that a feedback causality exists in long-run economic growth and financial innovation [lnGDPPC < == > lnM2/M1], which is supported by Bara and Mudxingiri (2016) and Mannah-Blankson and Belnye (2004), study also explored that feedback hypothesis is also prevail between [lnGDPPC < == > lnDCB], which is in line with results in the literature (Rana and Barua 2015). On the other hand, we also observed that financial development and economic growth support the feedback hypothesis over the long run [lnGDPPC < == > lnGCF], which is in line with results in the literature (Singh 2008).…”
Section: The Vecm Granger Causality Analysissupporting
confidence: 82%
“…This result implies that a feedback causality exists in long-run economic growth and financial innovation [lnGDPPC < == > lnM2/M1], which is supported by Bara and Mudxingiri (2016) and Mannah-Blankson and Belnye (2004), study also explored that feedback hypothesis is also prevail between [lnGDPPC < == > lnDCB], which is in line with results in the literature (Rana and Barua 2015). On the other hand, we also observed that financial development and economic growth support the feedback hypothesis over the long run [lnGDPPC < == > lnGCF], which is in line with results in the literature (Singh 2008).…”
Section: The Vecm Granger Causality Analysissupporting
confidence: 82%
“…Stulz (2000) finds evidence of that country's financial structure affects economic growth through its impact on how corporations raise and manage funds. In line with this, Singh (2008) finds presence of long-run equilibrium relationship between financial development and economic growth, while Vo (2010) and Wang (2009) emphasize the importance of Foreign Direct Investment (FDI) for this relationship. However, generally, the empirical literature does not give unanimous support to the theory.…”
Section: Introductionmentioning
confidence: 81%
“…2 The tendency of business corporations these days seems to be to splinter away financial functions and outsource them from specialized financial institutions. While the development of the financial infrastructure is a sine qua non for modern economic growth (Singh, 2008;Masih et al, 2009), the greater part of the product of financial institutions constitutes an intermediate input of other productive sectors. As such, and to that extent, the rapid growth of financial services (unlike final services like education and health) does not directly add to the aggregate value of final goods and services domestically produced (GDP).…”
Section: Introductionmentioning
confidence: 99%